Wartości interpersonalne a współdziałanie - Łukaszyński, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Individuality, co-operation between people, integration and the aim of human actions are determined by values. This article presents the interpersonal values of the average students group in the context of the M. Rokeach's test, according to his form E-4. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 35-43